Memory strategy instruction, contextual learning and ESP vocabulary recall - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
In the last decades there has been an increasing interest in vocabulary learning strategies given that they are found to facilitate second/foreign language vocabulary learning and recall. As many learners do not develop sufficient mastery of the strategy repertoire, explicit instruction on vocabulary learning strategies may help them to become more proficient with the broad range of strategies they can use through their vocabulary learning process. The present study investigates the effects of memory strategy instruction along with learning through context on the ESP vocabulary recall of Turkish EFL learners. The study further explores whether there is any difference in the use and choice of memory strategies of the learners as a result of such instruction. (c) 2006 The American University. Published by Elsevier Ltd. All rights reserved.
Keywords: KEYWORD METHOD; COMPREHENSION; MNEMONICS; LEARNERS